Microplásticos: caracterização e identificação em corpos hídricos do interior do estado de São Paulo - Schio, Natalí da Silva (2025)
Microplastics (MPs) are emerging contaminants widely distributed in aquatic environments, whose persistence and mobility have raised increasing concern within the scientific community. This study investigated the occurrence of MPs in four inland water bodies of São Paulo State, Brazil (Monjolinho, Jundiaí, and Tietê rivers, and Barnabé stream) between 2022 and 2024, and assessed their ecotoxicological effects on Chironomus sancticaroli. A total of 13,121 particles were quantified in water samples and 1,053 particles in sediments, with concentrations ranging from 0.11 to 4.38 items/L in water and from 59.05 to 379.97 items/kg in sediments. Seasonal variations were evident, with lower concentrations recorded during dry periods and higher concentrations during rainy periods, underscoring the role of rainfall in the surface transport of microplastics. Spatially, downstream sites of wastewater treatment plants exhibited higher concentrations, corroborating the hypothesis that these facilities function both as sinks and secondary sources of MPs. Physical characterization revealed a predominance of fragments and fibers, followed by films and microbeads. The most frequent colors in sediments were black (19.85%), white (16.14%), and brown (15.10%), while in water, they were black (22.5%), blue (16.7%), white (11%), and green (11%), suggesting predominantly secondary sources. Chemical characterization identified 32 polymer types, with polyethylene (PE; 32.3% in water, 29.8% in sediment), polypropylene (PP; 30.5% in water, 14.0% in sediment), and polyethylene terephthalate (PET; 8.9% in water, 10.7% in sediment) being the most abundant. In ecotoxicological bioassays, C. sancticaroli larvae were exposed to PP and PA 12 particles at three different concentrations. Although no statistically significant differences in mortality were detected. Importantly, the ingestion of MPs by this species was confirmed for the first time using Py-GC/MS, which detected characteristic chromatographic peaks of PA 12 in exposed larvae. This work constitutes the first integrated survey of MPs in rivers of São Paulo State, providing evidence regarding their sources, environmental dynamics, and interactions with benthic organisms. The findings emphasize the urgent need to include MPs in Brazilian environmental monitoring programs and contribute to the standardization of analytical protocols for future ecological risk assessments.